Perceptions of faculty on promotion policy in medical and dental colleges associated with Shaheed Zulfiqar Ali Bhutto Medical University Islamabad, Pakistan - Muhammad Riaz Shahbaz Janjua; Jamilah Janjua; Shazia Muazam; Gohar Wajid (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the perceptions of medical and dental faculty regarding the existing promotion criterion and develop a proposed alternative criterion. Method: The qualitative exploratory study was conducted from November 2019 to May 2020 at Shaheed Zulfiqar Ali Bhutto Medical University, Islamabad, Pakistan, after approval from the Islamic International Medical College which is affiliated with Riphah International University, Rawalpindi, Pakistan. It comprised focus group discussions involving experts from two medical and dental colleges from both private and public sectors. Data was analysed manually to develop codes, subthemes and themes. Results: Of the 24 participants, 12(50%) participated in each of the two focus groups discussions. Each discussion included 1(8.3%) principal, 2(16.7%) professors, 1(8.3%) associate professor, 2(16.7%) assistant professors and 1(8.3%) senior lecturer from basic sciences, and 1(8.3%) professor, 1(8.3%) associate professor and 1(8.3%) assistant professor from the clinical side as well as 1(8.3%) final year student each from the medical and dental streams. All 24(100%) believed that the current promotion criteria was unrealistic, inconsistent and biased, and lacked justified faculty evaluation; 19(80%) agreed on strengthening the role of research in promotion; 3(12.5%) highlighted lack of opportunities for post-graduation, and 18(75%) were in favour of introducing faculty e-portfolio. Collectively, they suggested that in order to make the criteria dependable, it should include comprehensive teacher assessment with mandatory continuing professional development activities, by standardising research work, and through introducing robust faculty promotion policy and guidelines. ---Continue